Biomass Derived Laser-Induced Graphene with Embedded Catalysts: Towards Enhanced Oxygen Reduction Reaction Catalytic Performance - aldhafeeri, Tahani (University of Waterloo, 2023)
Zinc-air batteries are viewed as one of the most promising energy storage technologies for consumer electronics, electric vehicles, and grid storage due to a number of benefits including relatively high theoretical specific energy density (1350 Wh/kgactive material ) compared to lithium-ion batteries (1000 Wh/kgactive material), the abundance of zinc in the earth, and its inherent safety and ease of handling. Zinc-air batteries (ZAB) include an air-breathing cathode in addition to more standard battery components including a metal (zinc) anode, polymer separator, and alkaline electrolyte. This makes ZABs a unique technological advancement. Unlike other common battery systems like lithium-ion batteries, which store active material in the cathode, the air cathode of a ZAB uses gaseous oxygen molecules in the air as the fuel for an energy-generating process. The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) processes that take place during battery discharge and charge, respectively, largely control the overall energy efficiency of the ZAB system due to their inherently slow kinetics. Nevertheless, the most significant obstacles to the large-scale industrial deployment of ZABs are their low round-trip energy efficiency and performance deterioration. Both issues are directly connected to the poor activity and stability of the electrocatalysts used to catalyze the reactions at the air electrode and the reactions at the zinc electrode. In order to substitute precious metal catalysts, a variety of hybrid catalysts, transition metal-based catalysts, and metal free catalysts have been studied. However, the majority involve complex fabrication processes that demand special conditions and multiple, often energy intensive steps. This has hindered scale-up and can result in additional costs. Consequently, a straightforward technique for creating air electrodes with active catalysts is essential. Laser induced carbonization has emerged as a promising, furnace-free approach to create carbon-based materials and electrodes in one step. However, little work has been carried out to determine whether precious and non-precious metal catalysts can also be formed during this rapid laser conversion process and whether such methods could result in high activity electrocatalysts for the air-cathode of a zinc-air battery. Thus, in this thesis, we sought to develop composites of carbon forming resins containing various precious and non-precious metal catalyst precursors that could be laser converted to high surface area carbon/catalyst composites. We successfully designed a simple approach to prepare air cathodes consisting of laser biomass-induced graphene (LIG) decorated by different catalysts; platinum based, manganese oxides, and metal free catalysts. We used furfuryl alcohol (FA) as a LIG precursor and CO2 laser to carbonize poly furfuryl alcohol instead of furnace in all the three projects. We demonstrate a facile approach to reduce platinum content to less than 2 wt.% by interfacing Pt with CoOx as well-dispersed nanoparticles entrapped within a highly conductive laser-induced graphene (LIG) matrix as an air-cathode for ZABs. Furfuryl alcohol was used as the monomer of poly furfuryl alcohol (LIG precursor) and as a reducing agent. Laser-induced carbonization of polymerized furfural alcohol pre-loaded with Co, and Pt precursors resulted in the formation of a mixture of spherical nanoalloys and core-shell Pt-CoOx structures with ultra-small size less than 2 nm. SEM, TEM and EDS analysis indicated excellent distribution of the nanoparticles consisting of core-shell (CoOx-Pt) and mixed spherical nanoalloys throughout the three-dimensional LIG. Moreover, the onset potential of LIG-PtCoOx air cathode is ~ +20 mV (vs. Hg/HgO) in alkaline media which indicates fast ORR kinetics when compared to commercial Pt/C (-30 mV vs. Hg/HgO) with the same catalyst concentration. The half-wave potential is -150 mV (vs. Hg/HgO) which is 30 mV more positive than commercial Pt/C. ZAB cycling using LIG-PtCoOx as catalyst material showed improved stability and rechargeability compared to the commercial Pt/C electrode. A greater peak power density of 67.1 mW/cm2 is also delivered by the LIG-PtCoOx cathode-assembled ZAB compared to the pricey Pt/C electrode (52.3 mW/cm2). Moreover, commercial manganese oxide (MnO2) was loaded in LIG via a facile one-pot polymerization reaction. Carbonization was accomplished by optimizing laser irradiation to produce a mixed-phase catalyst material supported by a highly conductive carbon matrix. Optimal loading of MnO/Mn3O4 vs LIG was determined via rotating ring disk electrode measurements where the samples that contained 10 wt.% MnO2 catalyst precursor (10MnxOy) had the best bifunctional performance towards ORR and OER and followed a four electron ORR pathway. While ZAB testing at 50 mA/cm2 indicated a voltage gap was 1.72 and 1.47 for the 10MnxOy composite and 20 wt.% Pt/C, respectively. The calculated power density showed peak powers at 48.3 and 69.0 mW/cm2 for 10MnxOy and 20 wt.% Pt/C, respectively. Finally, the synthesis method to fabricate metal free catalysts was studied using precursors entirely derived from waste biomass. Nitrogen doping of the LIG was achieved using chitosan as a biomass-based nitrogen source and furfuryl alcohol as the carbon precursor. The resulting nitrogen-doped LIG (N-LIG) samples were tested towards ORR performance. Reducing the size of the chitosan by ball milling was found to be a necessary pretreatment step to improve the ORR performance. To the best of our knowledge, this is the first work to utilize a nitrogen dopant in LIG for metal-free ORR electrocatalysis. In summary, we demonstrated the feasibility of preparing high performance ORR catalysis by laser-induced carbonization and reduction of various one-pot synthesized composite resins based on the biomass-derived poly furfuryl alcohol system. Recipes for low Pt-content Pt-Co-based alloys, manganese oxides and nitrogen doped carbons were found to achieve performance comparable or exceeding many literature studies and will, hopefully, form the basis of future advancement for practical air cathodes recipes which hold promise for low-cost zinc-air batteries and related electrochemical systems.
Keywords: zinc−air battery, air cathode, oxygen reduction reaction, laser-induced graphene, rotating ring disk electrode, poly(furfuryl alcohol), Triton X-100, chitosan, manganese oxide, platinum, cobalt, cobalt oxide, nitrogen doping, beads milling.